“La recreación infantil en el desarrollo de estructuración espacial en los niños de Educación Inicial” - Hurtado López, Johanna Maricela (2023)
The research carried out on children's recreation in the development of spatial structuring in children of Initial Education executed in the Basic Education School "Naciones Unidas" of the Saquisili Canton, has been of great importance since it benefited the students and teachers of the institution. The problem was the lack of recreational activities for spatial structuring. The objective of the work was to diagnose the development of spatial structuring through children's recreational activities in preschool children. The methodology is based on a qualitative approach, with a non-experimental research design, bibliographic type of research, using the observation technique and the interview with its corresponding instruments, observation sheet and question guide. For this reason, in this process, practical activities were carried out with each of the students considering each indicator of the observation sheet, based on the use of recreation for the development of spatial structuring. As a result of the interview it was found that the teacher in charge does not apply recreational activities in order to develop the spatial perception of infants. Thus obtaining a socio-educational impact because the teachers will be able to give greater importance to this topic, in fact, it will allow them to improve their knowledge for the teaching-learning process, thus creating a dynamic interaction. In this way, it is possible to